Regulation Requires Records: Access to Fracking Information in the Marcellus/Utica Shale Formations - Tansey, Eira (KULA)

(untitled) (University of Victoria Libraries, 2018)
In the world of environmental regulation, records are the foundation on which all further regulatory action takes place. From permits that give industry permission to pollute in the name of economic activity, to annual production reports documenting how much fossil fuel is taken out of the ground, notices of violation issued by regulators, to complaints filed by citizens noticing contaminants in their water supply, recordkeeping is fundamental to regulation. Even as records are critical to understanding and contextualizing environmental problems, accessing and interpreting this information is an exceptionally difficult experience. This article will consider the regulatory recordkeeping context of hydraulic fracturing (fracking) in Ohio, Pennsylvania, and West Virginia, the three most productive states in the Marcellus/Utica shale formation.